16S rRNA gene-based microbiota profiles from diverse avian faeces are largely independent of DNA preservation and extraction method - Edwards, Johnson; Hoffbeck, Carmen; West, Annie G.; Pas, An; Taylor, Michael W. (Frontiers in Microbiology, 2023)
The avian gut microbiota has been the subject of considerable recent attention, with potential implications for diverse fields such as the poultry industry, microbial ecology, and conservation. Faecal microbiotas are frequently used as a non-invasive proxy for the gut microbiota, however the extraction of high-quality microbial DNA from avian faeces has often proven challenging. Here we aimed to evaluate the performance of two DNA preservation methods (95% ethanol and RNAlater) and five extraction approaches (IndiSpin Pathogen Kit, QIAamp PowerFecal Pro DNA Kit, MicroGEM PrepGEM Bacteria Kit, ZymoBIOMICS DNA Miniprep Kit, and an in-house phase separation-based method) for studying the avian gut microbiota. Systematic testing of the efficacy of these approaches on faecal samples from an initial three avian species (chicken, ostrich, and the flightless parrot kākāpō) revealed substantial differences in the quality, quantity and integrity of extracted DNA, but negligible influence of applied method on 16S rRNA gene-based microbiota profiles. Subsequent testing with a selected combination of preservation and extraction method on 10 further phylogenetically and ecologically diverse avian species reiterated the efficacy of the chosen approach, with bacterial community structure clustering strongly by technical replicates for a given avian species. Our finding that marked differences in extraction efficacy do not appear to influence 16S rRNA gene-based bacterial community profiles provides an important foundation for ongoing research on the avian gut microbiota.